Bigstone Cree Nation : K-3 school curriculum and program framework - Yellowknee, Nora C; University of Lethbridge. Faculty of Education (Lethbridge, Alta. : University of Lethbridge, Faculty of Education, 1997, 1997)
85 leaves 28 cm. -- Our First Nations communities have been forced to experience different educational settings and from these experiences there has been a public outcry to meet the educational needs of our children. Meeting the educational needs of our children is a great challenge. It is an honour to be involved in a process of developing programs and curricula with people who are open and have committed themselves to providing a different learning experience for our First Nations children and have a deeper understanding of what it means to plan an education and that is in line with an holistic, or organismic, educational philosophy. As the process of developing culturally and linguistically appropriate curricula and programming gains acceptance, I hope our community people will come to see such a process as being necessary and realize that they have a prominent role to play in it and that they will offer their support in educating our children. Different areas of knowledge need to be explored and induded in order to enhance the learning/teaching experience of our children. This means inviting and involving Cree people, induding parents in the teaching/learning process, one which until now, they have eXlJerienced and accepted strictly as an activity that happens to them within the walls of a place called a school. Helping our Bigstone Cree Band/Nation (BCB/N) community people and parents to realize that education is broader in scope than what they have come to accept will be the biggest challenge to be met by Aboriginal or First Nations' educators.